Peningkatan Keterampilan Membaca Dan Menulis Arab Pegon Santri TPQ Al-Hikmah Sekuning Besowo Kepung Kediri - Siti Marfuah; Siti Nurjanah (LP3M IAIFA Kediri, 2022)
In order to preserve the tradition of writing using Pegon Arabic which is now rarely done, it is necessary to take action, one of which is through the learning of Pegon Arabic writing. Unfortunately, now Pegon's Arabic literacy teaching has weakened. This is evidenced by the facts that the author encountered regarding Pegon's Arabic literacy teaching. The partner of community service activities is TPQ Al-Hikmah, a hamlet of besowo village. Actually, the learning process at TPQ is not only focused on teaching to read the Qur'an but also learning about literacy using the Pegon Arabic script. But in the understanding of the pegon script is still very minimal. with the presence of this pegon arabic material. The research approach used in this study is the PAR ( Participatory Action Research) method. With the researcher program, namely